Behavior and Predatory Ability of Several Predatory Insects at Different Prey Densities - Junianto S. Batubara; Riska Romaito Nasution; Yosua Pangihutan Pardamean Alextio Sianturi; Mario Pani; Muhammad Sayuthi (Jurnal Biologi Tropis, 2026)
Understanding predator behavior and predation capacity is essential for determining their potential as biological control agents. This study aimed to evaluate the searching time, handling time, and predation ability of three predators Syrphidae larvae, Coccinella sp. larvae, and Curinus coeruleus adults at different prey densities. Five prey-density treatments (5, 10, 15, 20, and 25 individuals) were tested using3 Heteropsylla cubana as prey for C. coeruleus and Rhopalosiphum maidis for Syrphidae and Coccinella sp. The results showed that increasing prey density significantly shortened the searching time of all predators. C. coeruleus demonstrated the fastest searching ability, followed by Syrphidae and Coccinella sp. Handling time also varied among predators, with C. coeruleus requiring the shortest time due to its chewing-type mouthparts, compared with the piercing–sucking mouthparts of Syrphidae and Coccinella sp. Predation capacity differed across predators; only C. coeruleus successfully consumed all prey at every density within 6 hours, while the other predators reached satiation at higher densities. Overall, C. coeruleus exhibited the highest efficiency across all parameters, indicating its strong potential as an effective biological control agent. Increasing prey density consistently enhanced predation activity, highlighting the importance of prey availability in predator effectiveness.